2005
DOI: 10.1021/bm0505888
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube ReinforcedBombyx moriSilk Nanofibers by the Electrospinning Process

Abstract: Nanocomposite fibers of Bombyx mori silk and single wall carbon nanotubes (SWNT) were produced by the electrospinning process. Regenerated silk fibroin dissolved in a dispersion of carbon nanotubes in formic acid was electrospun into nanofibers. The morphology, structure, and mechanical properties of the electrospun nanofibers were examined by field emission environmental scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, Raman spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(100 citation statements)
references
References 47 publications
(60 reference statements)
1
97
1
1
Order By: Relevance
“…It was also observed that the mechanical properties of the composite nanofibers were decreased as increased the amount of MWNT, which are due to the poor dispersion of the P-MWNTs in the PCL matrix or agglomeration of MWNTs at high concentration. 43 The bead formation might be another possibility for the low mechanical properties of the P-MWNT/PCL nanofibers. The low mechanical properties for beaded nanofibers were also reported by Inai et al …”
Section: Instrumentationmentioning
confidence: 99%
“…It was also observed that the mechanical properties of the composite nanofibers were decreased as increased the amount of MWNT, which are due to the poor dispersion of the P-MWNTs in the PCL matrix or agglomeration of MWNTs at high concentration. 43 The bead formation might be another possibility for the low mechanical properties of the P-MWNT/PCL nanofibers. The low mechanical properties for beaded nanofibers were also reported by Inai et al …”
Section: Instrumentationmentioning
confidence: 99%
“…Most of the carbon nanotubes exhibit good cytotoxicity towards pathogenic organisms, with single-walled carbon nanotubes reported to be the most efficient. Well-aligned single walled carbon nanotube (SWNT) along the fibre axis of the bombyx mori silk nanofibre were produced by Ayutsede et al [246]. A very low concentration of SWNT (1 wt%) was enough to increase the crystallinity and mechanical properties.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…The brunauer-emmett-tellersurface area of resultant materials is increased for potential applications, such as adsorption of drugs, filtration, and sensor fabrication (54). Currently, the nano-nets can be fabricated from various materials, for instance, PA-6 (54), polyacrylic acid (55), poly(vinyl alcohol) (51), polyurethane (PU) (56), poly(trimethylene terephthalate) (57), gelatin (58) chitosan (59) and silk (60).…”
Section: Fibrous Structure Produced Via Phase Separation In An Electrmentioning
confidence: 99%